Production of Biofuel Crops in Florida: Sweet Sorghum - Wilfred Vermerris; John Erickson; David Wright; Yoana Newman; Curtis Rainbolt (EDIS)
Varieties of sorghum with a high concentration of soluble sugars are attractive as a potential energy crop because of the easy accessibility of readily fermentable sugars combined with very high yields of green biomass. Similar to sugarcane, the sap of sweet sorghum is extracted by milling, and can be easily fermented to produce ethanol. Other products from sweet sorghum include syrup, molasses, and crystal sugar. This revised 3-page fact sheet was written by Wilfred Vermerris, John Erickson, David Wright, Yoana Newman, and Curtis Rainbolt, and published by the UF Department of Agronomy, December 2011.